Compendium of statistics - African Development Bank Group; African Development Bank.; African Development Fund.; Nigeria Trust Fund.; African Development Bank. (Abidjan, Côte d'Ivoire : The Bank, 1997)
"The purpose of this Compendium of Statistics is to provide in a readily accessible form data on the activities of the African Development Bank, African Development Fund and the Nigeria Trust Fund for the period ..."--Page i.
French title varies slightly.
1995, 1996 available
SERBIB/SERLOC merged record
Ref
Keywords: Development banks; Banks and banking; Banks and banking; Development banks; Africa